EFFECTIVENESS OF BOOKLET ON HANDLING FALLS ON PARENTS WITH TOODLER CHILDREN IN RIAU ISLANDS AREA - Elsa Gusrianti; Rian Yuliyana; Indah Dwi Astuti; Muthia Deliana; Meisa Daniati; Chintya Apriyana Simanjuntak (Bajang Institute, 2023)
The age period of children 1 to 3 years is called toddler. Toddlers show more advanced motor development and children show more activity skills and develop curiosity, and exploration of objects around them. ). Factors that can cause accidents in toddlers include the presence of objects or materials such as bottles containing medicine, water tubs, and stairs to the 2nd floor. There are potential victims such as toddlers. Favorable environmental conditions include medicine bottles whose lids are not childproof, stairs that are not blocked, tubs filled with water that are more than 2 inches high, and lack of parental vigilance. This study aims to determine the picture of the effectiveness of booklets in parents on the problems of toddlers in island areas. The research method used is a quantitative approach with a quasi-experimental method (Quasi Experiment) type pretest-posttest control group design. The population in this study is tourists visiting Trikora Beach, Bintan Regency, and Riau Islands. The number of samples in this study was 68 people. Data collection techniques in this study were carried out using surveys/ interviews directly with respondents using questionnaires that had been tested for validity. Data analysis consists of univariate analysis and bivariate analysis. The results of the analysis showed that the Bivariate test obtained by Paired t-test 1 simple test was known to have differences in parental knowledge about handling due to the handling of children who fell obtained a P-value of 0.003 (<0.05) then Ho was rejected